The Research on the Optimal Control Strategy of a Serial Supply Chain Based on GA - Huang, Min; Ding, Jianqin; Ip, W. H.; Yung, K. L.; Liu, Zhonghua; Wang, Xingwei (Advances in Natural Computation, 2006)
Determination of optimal control strategy is one of the key factors for a successful supply chain management. This paper focuses on the research of an inventory control strategy of a serial supply chain. First, it proposes an optimization model of an inventory control that is based on the combination of a nonlinear integer programming model and the generally used push/pull control model. Then, the optimal control strategy is ratified by the fusion of genetic algorithm and simulation analysis. Case studies have demonstrated the effectiveness of the method.